As proibições de amaldiçoar a Deus e de maldizer o chefe do povo:um estudo das formulações jurídicas em Ex 22,27 - Jesus, Kleber Barreto de (2021)
The two legal formulations in Ex 22:27 offer several difficulties for their more accurate understanding. On the one hand, it is necessary to recognize the hebrew text and the poetic configuration of these two imperative laws. Although the two laws in question contain only seven words, several stylistic elements have been used to transform them into a small work of art. On the other hand, it is necessary to investigate the semantic load that, more precisely, belongs to each word used in the two legal formulations. Finally, there is the task of understanding and describing the theological reflection promoted by these Mosaic laws, presented as divine commandments. All of these studies start, above all, from looking closely at the decisive parallels, valuing the knowledge of the Alliance Code (Ex 20:22–23:33), the Book of Exodus, the Pentateuch and the Hebrew Bible